المشكلات التي تواجه مادة التر بية الفنية في مدارس المرحلة الثانوية بمدينة السليمانية من وجهة نظر مدرسيها و مقترحاتهم لحلها - حسين, جواد نعمت (Sulaimani Journal for Humanities, 2003)
The aim of this study is to identify the problems facing the subject of “Art Education in the secondary schools of Sulaimania City from the view point of the teachers and their proposed Solutions. The study is descriptive and based on a survey which covers (50) secondary schools and (50) teachers of the “Art Education”, (19 male and 31 female). The questionnaire was used to collect information its (Validity and Reliability was decluced). After the application of the questionnaire to the target groups. The data were processed statistically by using (fisher) equation. The results and up with (20) problems and (23) proposed solution.